Regulating the d-band center of Ru/CoMoO4 ternary heterostructure by interface engineering for accelerated hydrogen adsorption kinetics - Miao Ma; Min Yang; Cai-Yue Zhang; Hai-Yi Sun; Rong-Jing Su; Xiao-Rui Yue; Chen-Xi Li; Yong-Ming Chai; Bin Dong (Fuel, 2026)

A lyophilized RPA–CRISPR/Cas13d one-pot platform for rapid detection of porcine circovirus type 3 - Li-Na Shao; Zheng-Luo; Bao-Ling Liu; Tong-Xu; Yuan-Meng Wang; Jia-Qi Duan; Lei-Zhao; You-You Li; Yang-Ming Dai; Qin-Rui Jia; Le-Yi Zhang; Ling-Zhu; et al. (Analytica Chimica Acta, 2026)

Corrigendum to “TBBPA induced hepatocyte ferroptosis by PCBP1-mediated ferritinophagy” [J Hazard Mater 494 (2025) 138515] - Rui-Qi Liu; Yu-Tong Wu; Yue Cheng; Yuan-Hang Chang; Muhammad Asmat Ullah Saleem; Zi-Yan Hu; Shang-Jia Yang; Xue-Qi Wang; Yi-Jia Song; Xin-Yue Mao; Jing Zheng; Yi-Bo Wang; et al. (Journal of Hazardous Materials, 2026)

Exploring the mechanism of platycodon grandiflorum saponins in treating Mycoplasma pneumoniae pneumonia based on intestinal microbiota and metabolomics - Rui Shuang Ji; Yun Fei Yang; Chan Yu Wu; Zhen Jing Yang; Jin Zhao Du; Jing Huang Fu; Lin Yao; Wei Ming Wang (Food Bioscience, 2026)

High-throughput prediction of the lowest triplet excitation energies in organic photovoltaic acceptors using physics-guided excess-factor-corrected fragment descriptors - Lei Cheng; Rui-Cheng Qin; Peng Xie; Ming-Yang Li; Yue Ren; Guang-Yan Sun (Chemical Engineering Journal, 2026)

Unveiling the role of Fe doping and Mo leaching in Fe-MoNi4@NiMoOx bifunctional catalysts for water splitting - Rui Ming; Jingjing Du; Lijian Xu; Yong Xu; Zhao Liang; Qiao Liu; Dongjiang Yang; Qiliang Wei; Weiyou Yang; Qing Shi (Chemical Engineering Journal, 2026)

Hydrogel-encapsulated microalgae-bacteria consortia for resilient saline agriculture - Xiao-Jing Wang; Nan Wu; Xiao Yu; Si-Ming Li; Zi-Rui Yang; Zhi-Hai Zhong; Kang Wang; Hong-Li Cui; Cheng-Gang Ren; Song Qin (World Journal of Microbiology and Biotechnology, 2026)

One novel sesquiterpenoid from the fungus Pestalotiopsis clavata JSQ 12 isolated from the mushroom Lanmaoa asiatica - Zi-Lin Wang; Shuai-Ming Zhu; Yu Yang; Rui Xu; Xue Zhao; Chen Sun; Qian Luo; You-Zhi Zhang; Guo-Gang Zhang; Chang-Wei Li (Natural Product Research, 2026)

Dimefluthrin-induced multigenerational endocrine toxicity in zebrafish (Danio rerio) offspring via parental exposure - Wei-Guo Wang; Rui-Rui Li; Ming-Jun Yang; Jing-Ying Hu; Wen-Ping Xu; Li-Ming Tao; Yang Zhang (Pesticide Biochemistry and Physiology, 2026)

A heterotrophic nitrification and aerobic denitrification strain capable of antibiotic degradation: From function to mechanism - Jia-Ying Li; You-Wei Cui; Yuan Sui; Ji-Tao Yan; Xin-Yu Gu; Rui-Chun Yang; Ming-Xin Su; Ze-You Lu (Environmental Pollution, 2026)

Analysis of Arbuscular Mycorrhizal Fungal Community in Soil of Sugarcane at Different Tillage Depths - Qun-Qing Huang; Sheng Wang; Ying-Jie Nong; Kai-Mao Zhong; Yi-Cheng Su; Xiao-Juan Qin; Jin-Lian Zhang; Yi-Hao Kang; Ting-Su Chen; Shi-Yuan Zeng; Xi-Chao Deng; Ming-Guo Jiang; et al. (Sugar Tech, 2026)

A polar strapdown airborne gravimetry method based on the transverse coordinate system - Chao-bo Yu; Shao-kun Cai; Mei-ping Wu; Zhi-ming Xiong; Rui-hang Yu; Bai-nan Yang (Applied Geophysics, 2026)

SGDC-UIE: A Semantic Guidance Network with Degradation Consistency for Underwater Image Enhancement - Rui Ming; Jianshan Zhang; Taotao Lai; Haibo Luo; Jiancheng Yang (Journal of Marine Science and Engineering, 2026)
Underwater images often suffer from color distortion, low contrast, and structural blurring caused by wavelength-dependent absorption and scattering, which degrade both visual observation and downstream perception. Existing underwater image enhancement methods usually learn image-level restoration mappings, while the relationships among semantic regions, degradation patterns, and restoration responses are not fully exploited. In this paper, we propose a Semantic Guidance Network with Degradation Consistency for Underwater Image Enhancement (SGDC-UIE). Specifically, SGDC-UIE first extracts dense semantic responses from a frozen DINOv3 prior and converts them into foreground, boundary, and background region gates. These gates are then used to guide pseudo-physical degradation estimation, producing attenuation-like, transmission-like, illumination, structure, and background-light priors for region-aware restoration. These pseudo-physical priors are learned, bounded conditioning variables rather than calibrated estimates of underwater optical parameters. Based on these degradation conditions, a dual-branch restoration network corrects low-frequency color and illumination degradation while recovering high-frequency structural details through semantic-aware wavelet restoration. The color-restored and structure-restored outputs are further integrated by a degradation-consistent fusion gate, which adaptively balances visual fidelity and task-relevant structure preservation. In addition, grouped supervision with quality-anchor replay stabilizes task-aware fine-tuning and reduces visual-quality drift. Extensive experiments on paired and no-reference underwater enhancement benchmarks, semantic segmentation, and underwater object detection show that SGDC-UIE achieves competitive restoration quality and improves the usability of enhanced images for downstream perception.

Integrative multi-omics reveals NQO1-mediated airway epithelial injury as a key mechanism of bisphenol A–induced COPD - Rui Li; Shaobo Ge; Jin Liu; Yuer Li; Shiyuan Yao; Shuhan Ma; Yuanliang Sun; Xiao Li; Xia Yang; Jie Zhang; Ming Zhang (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)

How to make big data accessible to plant biologists and beyond: Ten years of lessons from TBtools - Junting Feng; Chengjie Chen; Ya Wu; Longjiang Fan; Zhang Zhang; Ming Chen; Haibao Tang; Guangchuang Yu; Jian Ren; Jingchu Luo; Yi Liao; Aiping Luan; et al. (Molecular Plant, 2026)

Experimental study on the wave mitigation characteristics of a grid-type flexible-membrane breakwater under regular waves - Chuan-Rui Li; Jing-Ping Wu; Ming-Liang Cai; Jun-Ao Kang; Chang-Zhe Chen; Hong Fan; Chen-Xia Liu; Shi-Yu Yang; Zi-Wen Xu (Ocean Engineering, 2026)

A Ca-MOF@COF composite and its in situ grown gel membrane for highly efficient capture of Cd2+ - Xue-Mei Liu; Chuang-Chuang Zhang; Kun Yang; Wei-Liang Jin; Guan-Lian Mo; Rui Liu; Hong-Xin Jiang; Hao-Jie Cui; De-Ming Kong (Journal of Cleaner Production, 2026)

Salinity decrease leads to recovery of filamentous bacterial bulking in moderately halophilic aerobic granules: Unraveling the role of fungi - Ze-You Lu; You-Wei Cui; Ya-Nan Mi; Xin-Yu Gu; Rui-Chun Yang; Ming-Xin Su; Jia-Ying Li (Bioresource Technology, 2026)

Theta-aurora dynamics: Ionospheric mapping of evolving magnetospheric plasma boundaries - Xin-Ming Chen; Zan-Yang Xing; Qing-He Zhang; Yong-Liang Zhang; Hui-Gen Yang; L. R. Lyons; K. Oksavik; S. E. Milan; Rui-Long Guo; Tong Xu; Bin-Bin Tang; Xiang-Yu Wang; et al. (Science China Earth Sciences, 2026)
The theta-aurora, an auroral feature bridging the nightside and dayside auroral oval under a northward interplanetary magnetic field (IMF), is closely linked to the energetic plasma evolving within the magnetosphere. While existing views emphasize that energetic plasma resides on closed field lines, the mechanism by which it is accelerated and precipitates on open field lines to form the theta aurora remains poorly understood. Here, we introduce a mechanism derived from multi-instrument observations of theta-aurora evolution in the Northern Hemisphere and simulations conducted using a global magnetohydrodynamics (MHD) model. The observations and simulations exhibit excellent agreement, revealing that the theta-aurora represents ionospheric projections of boundaries between distinct magnetospheric plasma. These different magnetospheric plasma, an energetic structure originating from the plasma sheet and the preexisting cold lobe plasma, develop a boundary with contrasting physical properties that drive localized plasma instabilities. Particle precipitation occurs at plasma boundary, and controls both the formation and temporal evolution of theta-aurora. Our findings provide critical insights into the coupling between the ionosphere and magnetosphere under northward IMF.

High-Frequency Signal Recovery via the Constraint of Reflection Structure in f-x Domain - Chong Sun; Nan-ying Lan; Duo-ming Zheng; Hao-nan Tian; Shi-kai Jian; Lang Yang; Zhi-fang Ran; Rui-dong Liu (Applied Geophysics, 2026)

Metabolic inflexibility across heart failure phenotypes: mechanisms and type-specific therapeutic implications - Li Chen; Xin-Rui Yang; Yan Jiang; Shi-Qi Cheng; Zhen-Xun Wan; Jin-Wen Wu; Ming-Tai Chen; Yuan-Yuan Li; Gang Luo; Meng-Nan Liu (Apoptosis, 2026)

Dynamic error elimination method of strapdown gravimeter based on artificial neural network - Shao-kun Cai; Yang Yu; Rui-hang Yu; Zhi-ming Xiong; Ju-liang Cao; Yan Guo; Bai-nan Yang; Kai-xin Luo; Mei-ping Wu (Applied Geophysics, 2026)

Cooling energy demand for maintaining frozen wall thickness in artificial ground freezing - Xu Li; Rui-ming Li; Xiao-kang Li; Shuang Liu; Zheng Yang (Tunnelling and Underground Space Technology, 2026)

Impact of habitat biotic factors on selective food hoarding in Brandt's voles - Shan-shan Sun; Tao Liu; Hai-rui Yang; Zhi-liang Zhang; Ya-nan Li; Ming Ming; Hao-ting Zhang; Hai-wen Yan; Xin Li; Lin-lin Li; Na Zhu; Xiao-dong Wu; et al. (Journal of Arid Environments, 2026)

Cell-specific gene expression plasticity in response to hypoxia promotes high-altitude adaptive evolution - Wen-Tian Wei; Ze Yan; Hui Wu; Ming-Liang Zhou; Dong-Xin Mo; Xing Wan; Rui Ma; Mei-Ming Wu; Jia-Hui Huang; Ya-Jing Liu; Ji Yang; Meng-Hua Li (Science China Life Sciences, 2026)

Nanoflower-like Co3S4/FeOOH heterostructure enables efficient norfloxacin degradation via synergistic radical-non-radical PMS activation - Yuerong Zhou; Ming Yi; Yu Zhao; Rui Yang; He Yan; Xiuwen Cheng (ENGINEERING Environment, 2026)

Prediction and application of water inrush in water-rich area of TBM construction deep buried tunnel - Fa-yong Gao; Kun Yang; Yan-qiang Cheng; Yong-tao Ma; Kang Fu; Ming-yang Tang; Jin-rui Duan (Applied Geophysics, 2026)

Driving factors on bacterial community of heterotrophic nitrification and aerobic denitrification in real wastewater treatment plants: Evidence from different latitudinal gradients in warm season - Rui-Chun Yang; You-Wei Cui; Zhen-Ying Li; Yuan Sui; Tong Ren; Xin-Yu Gu; Ming-Xin Su; Ze-You Lu (Journal of Water Process Engineering, 2026)

Insight into the enhancement effect of pristine and amino-functionalized MWCNTs@SiO2 on the CO2 absorption and solar-driven regeneration performance of alkaline deep eutectic solvent based nanofluid system - Wei Wang; Yang Tang; Yi-Ming Chen; Rui-Rui Zhou; Zhang-Mao Hu; Jin-Cheng Huang (Journal of Environmental Chemical Engineering, 2026)

Spatiotemporal relationships between mammal habitat suitability and recreational hiking intensity in Xiaowutaishan National Nature Reserve, China - Ming Yam Chan; Yue Cao; Zhicong Zhao; Pei Wang; Yunshuang Feng; Le Yu; Steve Carver; Xuehua Liu; Ruijia Zhu; Fengze Lin; Xialin Li; Yiqing Wang; et al. (Biological Conservation, 2026)

Simultaneous remediation of heavy metals in mining soil using nZVI-supported attapulgite - Jun Ren; Caili Tong; Hanru Ren; Ming Gao; Gui Ma; Yunmeng Li; Rui Zhu; Xuri Mu; Chun Yang; Ling Tao (Environmental Geochemistry and Health, 2026)

Who is the best allogeneic hematopoietic stem cell transplant donor for severe aplastic anemia? Data from the Chinese Bone Marrow Transplantation Registry Group (CBMTRG) - Zheng-Li Xu; Lan-Ping Xu; Shun-Qing Wang; De-Pei Wu; Xi Zhang; Su-Jun Gao; Ling-Hui Xia; Rui Xi; Jian-Min Yang; Qi-Fa Liu; Ming Jiang; Xiao-Sheng Fang; et al. (Science Bulletin, 2026)

Synergistic mechanism for greenhouse gases reduction, pollution control, and economic development in the plastic packaging industry: A coupled analysis of material, value, and environmental flows - Mingxuan Tuo; Ming Yang; Yifan Gu; Guangwen Hu; He Peng; Rui Li; Tong Liu; Yufeng Wu (Resources, Conservation and Recycling, 2026)

Comprehensive evaluation on potentiality and key bacterial community of heterotrophic nitrification and aerobic denitrification in real wastewater treatment plants - Rui-Chun Yang; You-Wei Cui; Zhen-Ying Li; Ming-Teng Li; Yuan Sui (Process Safety and Environmental Protection, 2026)

Static magnetic field coupled with control of sludge retention time enhancing nitrogen removal via heterotrophic nitrification-aerobic denitrification - Ming-Xin Su; You-Wei Cui; Rui-Chun Yang; Yuan Sui; Xin-Yu Gu; Jia-Ying Li; Ze-You Lu (Journal of Water Process Engineering, 2026)

Twinned structure–enhanced S-scheme heterojunction in Zn0.8Cd0.2@g-C3N4 for efficient CO2 photocatalytic reduction - Ming-yang Liu; Hao-wen Zhu; Qing-shan Wang; Cong Liu; Heng-fei Cui; Jun-ying Tang; Rui-tang Guo (Fuel, 2026)

Effect of roasting on the chemical profiles of white and black sesame seeds during accelerated storage - Hao Liu; Shu-Guang Gao; Ming-Zhe Sun; Mei-Qi Yang; Huai-Yang Cao; Ke-Xin Zhang; Min-Shu Hong; Rui-Fu Cui; Zhao Qin; Hua-Min Liu; Xue-Ya Wang; Zhi-Jie Li (Food Chemistry, 2026)

The yield-biomass-water-environment nexus model unravels the plastic mulching film dilemma: Yield gains vs. environmental cascades in China’s cotton systems - Yifan Gu; Zixin Bian; Qianqian Shi; Ziyi Zhao; Haixia Li; Rui Li; He Peng; Ming Yang; Qingbin Yuan; Yufeng Wu (Agricultural Systems, 2026)

tRNAGlu−CTC-1-1-derived small RNAs inhibit the proliferation of immature porcine Sertoli cells - Guo Ming; Cha Ding-rui; Yang Jin; Luo Jun; Zeng Wen-xian; Chen Xiao-xu (Theriogenology, 2026)

A one-step strategy for rapid detection of sub-50 nm polystyrene nanoplastics using nanobody-based homogeneous immunoassay - Yang Deng; Yang Guo; Fei Li; Ming Zhang; Yuansheng Yang; Rui Nian; Wenshuai Liu (Journal of Hazardous Materials, 2026)

Alkalinity change induces succession of heterotrophic and autotrophic nitrifying bacterial communities: Comprehensive insights on the mechanism - Yuan Sui; You-Wei Cui; Rui-Chun Yang; Ya-Nan Mi; Xin-Yu Gu; Jia-Ying Li; Ming-Xin Su (Journal of Environmental Management, 2026)

Gastrin releasing peptide receptor antagonism in the paraventricular nucleus exerts antihypertensive effects in 2K1C rats - Xiao-Min Wang; Jin-Jun Liu; Yi-Pu Wang; Chao Bai; Abdoulaye Issotina Zibrila; Wen-Jie Xia; Rui-Na Yang; Yu-Ming Kang; Xiao-Jing Yu (Toxicology and Applied Pharmacology, 2026)

Enhancement role of corncob slow-release carbon source on heterotrophic nitrification and aerobic denitrification process in low C/N wastewater treatment - Xin-Yu Gu; You-Wei Cui; Yuan Sui; Jia-Ying Li; Ming-Xin Su; Ze-You Lu; Rui-Chun Yang (Journal of Environmental Management, 2026)

Recent progress on Cu-based MOF electrocatalysts for CO2 reduction - Heng-fei Cui; Xiao-jing Liu; Cong Liu; Hao-wen Zhu; Ming-yang Liu; Rui-tang Guo (Fuel, 2026)

Comprehensive assessment of secondary metabolite diversity and in vitro anti-diabetic properties in Sanghuangporus quercicola cultured under different conditions - Mingxing Yu; Na Zhang; Xiaofeng Ma; Xiaoshuang Zhou; Shude Yang; Weihang Peng; Yin Li; Yuejun Mu; Xianhao Cheng; Rui Zhang; Yongfei Ming (Systems Microbiology and Biomanufacturing, 2026)

Mechanisms of Action of FUNDC1 in Cerebral Ischemia-Reperfusion Injury - Xin-Yi Zou; Luo-Yang Cai; Jin Zhang; Ying Yuan; Jie Song; Zhao-Duan Hu; Rui Peng; Xiao-Feng Ruan; Xiao-Ming Zhang (Molecular Neurobiology, 2026)

Two meroterpenoids from the root bark of Eucalyptus robusta - Yi-Yang Chen; Yong-Xin Wei; Rui-Zhen Chen; Kun-Feng Zhang; Ling-Yi Kong; Ming-Hua Yang (Phytochemistry Letters, 2025)

Precise construction of Anderson-type polyoxometalate-based covalent organic frameworks for photocatalytic hydrogen peroxide production - Zhang-Di Liu; Zai-Xiang Zhang; Yang Yang; Rui Xing; Zi-Hao Wei; Hou-He Liu; Jiang-Bo Ming; Jin Zhu; De-Yin Wang (Journal of Water Process Engineering, 2025)

Tailored SO2 capture in multivariate UiO-66(Zr) MOFs: Experimental insights and theoretical mechanisms - Zai-Dong Shao; Peng Wu; Fang Liu; Qi-Jun Zhang; Chao-Yang Guo; Rui-Sang Liu; Jiang Lu; Xiao-Meng Ren; Yu-Ming Zheng (Journal of Environmental Chemical Engineering, 2025)

Temporal transcriptomics reveal crucial networks underlying jasmonate-mediated diurnal floret opening and closure in rice - Rui Zhang; Xiaohui Xi; Xiaozhou Hu; Dan Xiang; Yi Wang; Yu Pan; Xi He; Yuhan Zhang; Lilan Hong; Yuanzhu Yang; Ming Zhou (Science China Life Sciences, 2025)

CRP and HNF1A collaborate to regulate the progression of laryngeal cancer through the Wnt signaling pathway - Zhigang Zhao; Xiaojing Zhu; Jinyuan Xu; Penglong Song; Yanan Sun; Zhenming Yang; Li Wang; Jiarui Zhang; Rui Zhao; Xiaoxue Chen; Wenjing Li; Linli Tian; et al. (Functional & Integrative Genomics, 2025)

Bioactive sulfur-containing amides from the leaves of Glycosmis lucida - Shou-Yuan Wu; Hong-Yan Yang; Zhong-Liu Zhou; Zi-Feng Liang; Rui-Hong Zhu; Jing-Ling Ren; Pei-Lian Liu; Zi-Ming Chen (Natural Product Research, 2025)

Partial nitrification achievement through co-regulation of quorum sensing-mediated boric acid and free ammonia - Xu-Ming Liu; Bai-Hang Zhao; Hai-Shan Yang; Rui-Xuan Liu; Lei-Yue Wu (Journal of Water Process Engineering, 2025)

Stress migration and failure mechanisms of rocks with holes under gradient stress conditions - Xingyu Wu; Ming Tao; Zheng Yang; Ziheng Xiao; Rui Zhao; Shaofeng Wang (International Journal of Rock Mechanics and Mining Sciences, 2025)

Efficient synthesis of FePO4 from the incinerated sewage sludge ash by modification–selective leaching–precipitation - Zhong-hua Yang; Chuan-ming Du; Pei-yuan Ni; Lei Yuan; Yu-tang Zhang; Rui-yuan Yuan (Chemical Engineering Journal, 2025)

Marine Hydrogen Pressure Reducing Valves: A Review on Multi-Physics Coupling, Flow Dynamics, and Structural Optimization for Ship-Borne Storage Systems - Heng Xu; Hui-Na Yang; Rui Wang; Yi-Ming Dai; Zi-Lin Su; Ji-Chao Li; Ji-Qiang Li (Journal of Marine Science and Engineering, 2025)
As a zero-carbon energy carrier, hydrogen is playing an increasingly vital role in the decarbonization of maritime transportation. The hydrogen pressure reducing valve (PRV) is a core component of ship-borne hydrogen storage systems, directly influencing the safety, efficiency, and reliability of hydrogen-powered vessels. However, the marine environment—characterized by persistent vibrations, salt spray corrosion, and temperature fluctuations—poses significant challenges to PRV performance, including material degradation, flow instability, and reduced operational lifespan. This review comprehensively summarizes and analyzes recent advances in the study of high-pressure hydrogen PRVs for marine applications, with a focus on transient flow dynamics, turbulence and compressible flow characteristics, multi-stage throttling strategies, and valve core geometric optimization. Through a systematic review of theoretical modeling, numerical simulations, and experimental studies, we identify key bottlenecks such as multi-physics coupling effects under extreme conditions and the lack of marine-adapted validation frameworks. Finally, we conducted a preliminary discussion on future research directions, covering aspects such as the construction of coupled multi-physics field models, the development of marine environment simulation experimental platforms, the research on new materials resistant to vibration and corrosion, and the establishment of a standardized testing system. This review aims to provide fundamental references and technical development ideas for the research and development of high-performance marine hydrogen pressure reducing valves, with the expectation of facilitating the safe and efficient application and promotion of hydrogen-powered shipping technology worldwide.

SIRT3 promotes mitophagy to attenuate fumonisin B1-induced chicken hepatocyte senescence and antagonism of lycopene - Yuan-Hang Chang; Ming-Shan Chen; Hong-Mei Zhu; Rui-Qi Liu; Zi-Yan Hu; Shang-Jia Yang; Xue-Qi Wang; Yue Cheng; Yi-Jia Song; Xin-Yue Mao; Jing Zheng; Yi-Bo Wang; et al. (Journal of Hazardous Materials, 2025)

Experimental investigation on mechanical behaviors and shear fracture mechanisms of rough jointed sandstone under conventional triaxial compression - Sheng-Qi Yang; Ming-Hui Cao; Rui Yong; Shi-Gui Du; Cheng Zhao; P.G. Ranjith (International Journal of Rock Mechanics and Mining Sciences, 2025)

Sunlight-activated photochromic-photothermal nanofibrous textiles for self-monitored thermal management - Shuai Liang; An-Yang Duan; Shi-Kun Yan; Yan-Rui Zhao; Jin Zhang; Guo-Wei Xiao; Chang-Hai Xu; Ji-Xiang Hu; Guo-Ming Wang (Chemical Engineering Journal, 2025)

In/S co-decorated SnSe encapsulated in a dual carbon layer for sodium ion storage - Ya Ru Pei; Yong Jin Xia; Lei Ming Wang; Rui Li; Jun Xi Peng; Xue Jing Yang; Jian Li; Chun Cheng Yang; Qing Jiang (Chemical Engineering Journal, 2025)

Achieving stable partial nitrification through AHL-mediated quorum sensing combined with free ammonia: performance, microbial responses, and mechanistic insights - Bai-Hang Zhao; Xu-Ming Liu; Hai-Shan Yang; Rui-Xuan Liu; Lei-Yue Wu (Chemical Engineering Journal, 2025)

Anti-inflammatory and antinociceptive effects, toxicity, and phytochemical analysis of Beaumontia grandiflora Wall. - Rui Yang; Dan Teng; Ming-rui Yang; Yi-huan Li; Jian-fen Xiao; Qian-ru Zhang; Hong-ping He; Hua-yi Jiang (Natural Product Research, 2025)

First experiment using post-accelerated unstable ion beams at BRIF: angular distribution of the 21 , 22 Na elastic scattering from doubly magic 40 Ca - Wei Nan; Bing Guo; Cheng-Jian Lin; Dan-Yang Pang; Lei Yang; Dong-Xi Wang; Guo Yang; Yang-Ping Shen; Bing Tang; Qi-Wen Fan; Yi-Wen Bao; Lei Cao; et al. (Science Bulletin, 2025)

Comparative metagenomic analyses of viral genomic diversity and ecosystem functions in extremely acidic copper mine tailings - Pei-Zhe Ye; Qiang Yang; Chu-Yi Zhang; Tao-Tao Yang; Sheng-Fang Jiang; Rui Lan; Shao-Ming Gao; Li-Nan Huang (Journal of Hazardous Materials, 2025)

A novel forward osmosis nanocomposite membrane with g-C3N4 quantum dots fabricated on polyacrylonitrile electrospun nanofiber membrane for high-permeability and selectivity - Dibakar Pandaya; Jia-Rui Yang; Zhen-Liang Xu; Mateen Hedar; Ming-Xiao Zhang; Rui Jia; Rui Han; Muhammad Irfan; Liang Cheng; Mahesh Kumar Joshi (Chemical Engineering Journal, 2025)

Two alkenyl phenol derivatives from the fungus Pestalotiopsis clavata JSQ 12 isolated from the mushroom Lanmaoa asiatica - Jing Tang; Rui Xu; Hao Ma; Shuai-Ming Zhu; Fu-Yao Luo; Xue Zhao; Ya-Shuai Kang; Yuan-Wei Gao; Yu Yang; Chang-Wei Li (Natural Product Research, 2025)

Chinese Tuina ameliorates muscle damage by regulating endoplasmic reticulum stress and autophagy in a rat model of skeletal muscle contusion - Hai-chao Liu; Hao-ming Zhu; Ming Li; Bo-rui Chen; Zheng-yu Yang; Yu Wang; Shi-zhong Wang; Shao-qing Chen; Jian-ping Lin (Tissue and Cell, 2025)

A new benzoquinone and a new dihydroflavone from Fissistigma polyanthum and their bioactivity - Jian-Fen Xiao; Ming-Rui Yang; Pin-Xiang Fu; Rui Yang; Hong-Ping He; Hua-Yi Jiang (Phytochemistry Letters, 2025)

TBBPA induced hepatocyte ferroptosis by PCBP1-mediated ferritinophagy - Rui-Qi Liu; Yu-Tong Wu; Yue Cheng; Yuan-Hang Chang; Muhammad Asmat Ullah Saleem; Zi-Yan Hu; Shang-Jia Yang; Xue-Qi Wang; Yi-Jia Song; Xin-Yue Mao; Jing Zheng; Yi-Bo Wang; et al. (Journal of Hazardous Materials, 2025)

Sustainable remediation of butyl xanthate-contaminated mine wastewater by combining emergent macrophyte Cyperus alternifolius with a versatile bacterial isolate - Qi Liu; Yao-Yao Ye; Sha Yang; Cheng-Yu Cui; Huan Du; Jin-Cheng Ye; Ji-Liang Cheng; Rui-Wen Hu; Lei Xiang; Bai-Lin Liu; Yan-Wen Li; Quan-Ying Cai; et al. (Journal of Hazardous Materials, 2025)

Strain-specific effects of fish originated Bacillus velezensis on growth, gut health, and disease resistance of zebrafish - Yuan-Yuan Yao; Wen-Hao Zhou; Juan Hu; Ya-Lin Yang; Ming Li; Rui Xia; Chao Ran; Zhen Zhang; Zhi-Gang Zhou (Fish & Shellfish Immunology, 2025)

Functional nucleic acid-stabilized selenium nanotechnology enable synergistic healing of diabetic chronic wounds - Si-Wei Yang; Jing Wang; Yan Tan; Xiao Jing; Chen-Yu Wang; Zhi-Li Yao; Wen-Hui Wang; Yong-Ji Li; Hao-Rui Li; Yan Zhao; De-Ming Kong; Qi-Liang Cai (Chemical Engineering Journal, 2025)

Recyclable flame retardant, luminescent, and transparent thermoplastic polyurethanes: applications in light conversion films for flexible solar cells - Li-Wei Su; Ming-Hao Liu; Yang Jing; Peng-Yu Huang; Bo Jiang; Rui-Guang Xing; Xin Ge; Ya-Hui Li; Jin-Xiao Bao; Gao-Fei Pan (Chemical Engineering Journal, 2025)

Calcium-O-Sr-Nd isotope evidence for the origin of REE-bearing carbonatite from metasomatized lithospheric mantle without recycled carbonate - Xing-Hui Li; Ming-Cai Xie; Kui-Feng Yang; Kan Li; Chun-Ming Han; Hai-Dong She; Gai-Zhong Liang; Xiao-Chun Li; Hong-Rui Fan (Contributions to Mineralogy and Petrology, 2025)

Molecular identification of heterotrophic nitrification and aerobic denitrification bacteria: From methods development to application demonstration - Rui-chun Yang; You-wei Cui; Zhen-ying Li; Ming-teng Li; Liu-xu Jiang; Ya-nan Mi; Yuan Sui; Hui-kai Liang (Water Research, 2025)

The recruitment of alkaline phosphatase-positive endogenous neural stem cells enables robust neurogenesis and neural pathways reconstruction following spinal cord injury - Rong-Jie Wu; Jia-Lin Liu; Zheng-Hong Chen; Jing Xu; Ying Ding; Hai-Yang Yu; Chuang-Ran Wu; Shang-Bin Yang; Rui Liu; Yi-Nan Guo; Yue Yang; Ting-Ting Wu; et al. (Chemical Engineering Journal, 2025)

Epigenetics in the modern era of crop improvements - Yan Xue; Xiaofeng Cao; Xiangsong Chen; Xian Deng; Xing Wang Deng; Yong Ding; Aiwu Dong; Cheng-Guo Duan; Xiaofeng Fang; Lei Gong; Zhizhong Gong; Xiaofeng Gu; et al. (Science China Life Sciences, 2025)
Epigenetic mechanisms are integral to plant growth, development, and adaptation to environmental stimuli. Over the past two decades, our comprehension of these complex regulatory processes has expanded remarkably, producing a substantial body of knowledge on both locus-specific mechanisms and genome-wide regulatory patterns. Studies initially grounded in the model plant Arabidopsis have been broadened to encompass a diverse array of crop species, revealing the multifaceted roles of epigenetics in physiological and agronomic traits. With recent technological advancements, epigenetic regulations at the single-cell level and at the large-scale population level are emerging as new focuses. This review offers an in-depth synthesis of the diverse epigenetic regulations, detailing the catalytic machinery and regulatory functions. It delves into the intricate interplay among various epigenetic elements and their collective influence on the modulation of crop traits. Furthermore, it examines recent breakthroughs in technologies for epigenetic modifications and their integration into strategies for crop improvement. The review underscores the transformative potential of epigenetic strategies in bolstering crop performance, advocating for the development of efficient tools to fully exploit the agricultural benefits of epigenetic insights.

Synergistic reduction of pollutants and GHGs in China's PET industry: A material metabolism perspective - Fu Guo; Rui Li; Yifan Gu; Mingxuan Tuo; Zixin Bian; Yihan Li; Qingbin Yuan; Ming Yang; Yufeng Wu (Resources, Conservation and Recycling, 2025)

Recovery of volatile ethanol gas via microalgal-bacterial consortium: Ethanol-to-acetate conversion pathway boosts lipid production - Liu-Xu Jiang; You-Wei Cui; Ya-Nan Mi; Dong-Xu Zhou; Ming-Teng Li; Rui-Chun Yang (Journal of Environmental Management, 2025)

Assessing ecosystem integrity in protected areas: A systematic review of methods and applications - Yunshuang Feng; Yue Cao; Ming Yam Chan; Zhangqian Ye; Zhicong Zhao; Le Yu; Yongliang Liang; Steve Carver; Rui Yang (Biological Conservation, 2025)

CORBES: Radiation belt survey with international small satellite constellation - Ji Wu; Li Deng; Jaan Praks; Marius Anger; Philipp Oleynik; Wojciech Hajdas; Jin-Dong Wang; Shen-Yi Zhang; Bin Zhou; Li Zeng; Jinbin Cao; David Fischer; et al. (Advances in Space Research, 2025)

Preparation and epitope identification of a novel monoclonal antibody against 3A protein of Senecavirus A - Xiang-hui Ling; Biao Zhang; Hao-jie Ren; Ming-yang Li; Shun-da Liu; Meng-ru Luo; Ke-wei Guo; Shi-chong Han; Wen-rui He; Gai-ping Zhang; Yu-hang Zhang; Bo Wan (Veterinary Microbiology, 2025)

Molecular identification of three cytochrome P450 genes and their potential roles in insecticides tolerance in Grapholita molesta (Busck) - Hui Han; Ming-Gao Li; Kai-Yang Xing; Qi Wang; Jun Hu; Zhi-Guo Zhao; Qin Yu; Rui-Yan Ma; Ling-Ling Gao; Yan-Qiong Guo (Pesticide Biochemistry and Physiology, 2025)

Terrestrial ecosystem response to Early Cretaceous global environmental change: A calibrated, high-resolution Aptian record from Northeast China - Ming-Dao Sun; Qin Lin; Jahandar Ramezani; Jiang-Si Liu; Zheng-An Lu; Han-Qing Yang; Jiang-Hao Bai; Shi-Xi Cai; Jun-Cai Chen; Xuan-Yu Chen; Hao Cui; Guang-Chao Deng; et al. (Earth and Planetary Science Letters, 2025)

Strategic regulation of crystallization kinetics to achieve efficient pure-red quasi-2D perovskite light-emitting diodes - Yunhui Kuang; Yazhuo Xue; Zheng Zhang; Lvpeng Yang; Tong Bie; Rui Li; Wenxi Liang; Naigen Zhou; Ming Shao (Chemical Engineering Journal, 2025)

Estradiol Enhances Cerebellar Molecular Layer Interneuron-Purkinje Cell Synaptic Transmission and Improves Motor Learning Through ER-β in Vivo in Mice - Yong-Rui Piao; Mei-Rui Li; Ming-Ze Sun; Yang Liu; Chao-Yue Chen; Chun-Ping Chu; Yuki Todo; Zheng Tang; Chun-Yan Wang; Wen-Zhe Jin; De-Lai Qiu (The Cerebellum, 2025)

A high-available segmentation algorithm for corn leaves and leaf spot disease based on feature fusion - Falin Guo; Caihua Yao; Rui Yang; Miaomiao Ma; Xiaojiang Wu; Zihan Xu; Ming Lu; Jie Zhang; Guoshu Gong (Crop Protection, 2025)

TDCPP promotes apoptosis and inhibits the calcium signaling pathway in human neural stem cells - Ming-Rui Li; Guo-Rui Zhou; Zi-Ye Wang; Bo-Yang Li; Shu-Hui Men; Zhen-Guang Yan (Science of The Total Environment, 2025)

Bioconversion of agriculture by-products with functionally enhanced Streptomyces sp. SCUT-3: Fish skin as a model - Jing-Tao Ni; Ming-Shu Zhang; De-lin Lu; Wen-jun Lu; Lei Wu; Zhen-dong Yang; Can Qin; Zhen-jie Dai; Zhi-wei Li; Wen-jing Feng; Hua-hong Cai; Jia-rui Zhang; et al. (Food Chemistry, 2025)

H-NS-Mediated Regulation of Swimming Motility and Polar Flagellar Gene Expression in Vibrio parahaemolyticus - Yue Zhou; Jingyang Chang; Feng Li; Mei He; Rui Li; Yaqin Hou; Yiquan Zhang; Renfei Lu; Ming Yang (Current Microbiology, 2025)

AHR activation relieves deoxynivalenol-induced disruption of porcine intestinal epithelial barrier functions - Zi-Yan Hu; Shang-Jia Yang; Yuan-Hang Chang; Xue-Qi Wang; Rui-Qi Liu; Fu-Wei Jiang; Ming-Shan Chen; Jia-Xin Wang; Shuo Liu; Hong-Mei Zhu; Yu-Sheng Shi; Yi Zhao; et al. (Journal of Hazardous Materials, 2024)

Construction mechanisms, synthesis strategies, and photocatalytic applications of homojunction catalysts: A review - Hao-wen Zhu; Rui-tang Guo; Qing-shan Wang; Cong Liu; Heng-fei Cui; Ming-yang Liu; Wei-guo Pan (Journal of Environmental Chemical Engineering, 2024)

Molecular engineering in thizolo[5,4-d]thiazole-based donor-acceptor covalent organic framework Induced high-efficient photosynthesis of H2O2 - Ding-Ming Xue; Yi-Jun Zhang; Jing-Wen Chen; Hao Yang; Rui-Jie Xie; Shi-Chao Qi; Yuan-Qing Bu; Fei Liu; Hou-Hu Zhang; Jacques Lalevée (Chemical Engineering Journal, 2024)

Unraveling the chloride ion capture capability of nitrogen-doped porous carbon for capacitive deionization and desalination battery - Huazeng Yang; Rui Zhang; Zhiyuan Liu; Xin Xu; Yishuo Teng; Ming Hou; Guangshuai Zhang; Yongzhao Hou; Guangwu Wen; Dong Wang (Chemical Engineering Journal, 2024)

EtROP38 suppresses apoptosis of host cells infected with Eimeria tenella by inhibition of the p38MAPK pathway - Bu-ting Duan; Hao-yu Zhang; Zi-hao Song; Xiao-yi Han; Kai-ling Cui; Tong Xu; Yu Zhang; Yong-juan Zhao; Xuan Lei; Fan Tan; Lu-lu Guo; Hui-lin Yang; et al. (Veterinary Parasitology, 2024)

Corrigendum to “Euphpepluone S, a new lathyrane diterpenoid with anti-inflammatory activity from Euphorbia peplus L.” [Phytochem. Lett. 55 2023, 61–66] - Shi-Peng Guan; Ying Yang; Mao Sun; Min Cai; Xue-Xue Pu; Jian-Yi Huang; Ping Yi; Lin Liu; Ming-Rui Yuan; Yuan-Yuan Cheng; Ying-Tong Di (Phytochemistry Letters, 2024)

Macroalgal fossil Longfengshania from the Tonian Shiwangzhuang and Jiuliqiao formations in western Shandong and northern Anhui, North China - Guang-Jin Li; Lei Chen; Ke Pang; Qing Tang; Cheng-Xi Wu; Rui Huang; Ming-Yang Qiu; Xun-Lai Yuan; Chuan-Ming Zhou (Palaeoworld, 2024)

A Cysteinyl-tRNA Synthetase Mutation Causes Novel Autosomal-Dominant Inheritance of a Parkinsonism/Spinocerebellar-Ataxia Complex - Han-Kui Liu; Hong-Lin Hao; Hui You; Feng Feng; Xiu-Hong Qi; Xiao-Yan Huang; Bo Hou; Chang-Geng Tian; Han Wang; Huan-Ming Yang; Jian Wang; Rui Wu; et al. (Neuroscience Bulletin, 2024)
This study aimed to identify possible pathogenic genes in a 90-member family with a rare combination of multiple neurodegenerative disease phenotypes, which has not been depicted by the known neurodegenerative disease. We performed physical and neurological examinations with International Rating Scales to assess signs of ataxia, Parkinsonism, and cognitive function, as well as brain magnetic resonance imaging scans with seven sequences. We searched for co-segregations of abnormal repeat-expansion loci, pathogenic variants in known spinocerebellar ataxia-related genes, and novel rare mutations via whole-genome sequencing and linkage analysis. A rare co-segregating missense mutation in the CARS gene was validated by Sanger sequencing and the aminoacylation activity of mutant CARS was measured by spectrophotometric assay. This pedigree presented novel late-onset core characteristics including cerebellar ataxia, Parkinsonism, and pyramidal signs in all nine affected members. Brain magnetic resonance imaging showed cerebellar/pons atrophy, pontine-midline linear hyperintensity, decreased rCBF in the bilateral basal ganglia and cerebellar dentate nucleus, and hypo-intensities of the cerebellar dentate nuclei, basal ganglia, mesencephalic red nuclei, and substantia nigra, all of which suggested neurodegeneration. Whole-genome sequencing identified a novel pathogenic heterozygous mutation (E795V) in the CARS gene, meanwhile, exhibited none of the known repeat-expansions or point mutations in pathogenic genes. Remarkably, this CARS mutation causes a 20% decrease in aminoacylation activity to charge tRNA Cys with L-cysteine in protein synthesis compared with that of the wild type. All family members carrying a heterozygous mutation CARS (E795V) had the same clinical manifestations and neuropathological changes of Parkinsonism and spinocerebellar-ataxia. These findings identify novel pathogenesis of Parkinsonism-spinocerebellar ataxia and provide insights into its genetic architecture.

Transient response of semi-elliptical hill with an elliptical tunnel under blast and seismic loading - Hao Luo; Ming Tao; Zheng Yang; Rui Zhao; Chengqing Wu (Soil Dynamics and Earthquake Engineering, 2024)

Activation AMPK in Hypothalamic Paraventricular Nucleus Improves Renovascular Hypertension Through ERK1/2-NF-κB Pathway - Li-Yan Fu; Yu Yang; Rui-Juan Li; Abdoulaye Issotina Zibrila; Hua Tian; Xiu-Yue Jia; Jin-An Qiao; Jin-Min Wu; Jie Qi; Xiao-Jing Yu; Yu-Ming Kang (Cardiovascular Toxicology, 2024)

The mitigation of citric acid on cadmium toxicity in Iris tectorum and its effects on the composition of cell walls - Xiao-Fang Yu; Zhi-Wen Wang; Feng-Lian Chen; Mao-Lin Chen; Xin-Yu Zhang; Jun-Rui Zhang; Wen-Yu Ji; Xue Xiao; Li-Juan Yang; Ting Lei; Xi Li; Ming-Yan Jiang (International Biodeterioration & Biodegradation, 2024)

Mantle-rooted fluid pathways and world-class gold mineralization in the giant Jiaodong gold province: Insights from integrated deep seismic reflection and tectonics - Li-Qiang Yang; Jun Deng; Liang Zhang; Ai-Hua Zhao; M. Santosh; Xue-Feng Yu; Wei Yang; Da-Peng Li; Wei Shan; Dong Xie; Xiang-Dong Liu; Xue Gao; et al. (Earth-Science Reviews, 2024)

Gradient lithiophilic structure for the homogenized electric field strength to achieve dendrite-free lithium metal anode - Yan Dong; Rui Wang; Jianhua Wang; Zhenshan Yang; Longfei Li; Qianhui Wu; Lubin Ni; Guowang Diao; Ming Chen (Chemical Engineering Journal, 2024)

Engineering disease-resistant plants with alternative translation efficiency by switching uORF types through CRISPR - Jingjing Tian; Zhijuan Tang; Ruixia Niu; Yulu Zhou; Dan Yang; Dan Chen; Ming Luo; Rui Mou; Meng Yuan; Guoyong Xu (Science China Life Sciences, 2024)

Phylogenetic origin of an insect fauna at the boundary of the Palaearctic and Oriental realms: Evidence from ‘site‐based’ mitogenomics - Rui‐E Nie; Lu‐Lu Li; Anderson Feijó; Mei‐Xia Yang; Ming Bai; Thomas J. Creedy; Xu Jin; Jia‐Sheng Hao; Yong‐Ying Ruan; Hua‐Xi Liu; Beulah H. Garner; Ladislav Bocak; et al. (Journal of Biogeography, 2024)
Aim Knowledge of taxonomy and species distributions in highly diverse lineages of invertebrates remains too incomplete for the study of biogeographical patterns at the global scale. This limits the understanding of processes leading to the formation and maintenance of boundaries between major biogeographical realms. Site‐based metagenomic approaches may provide an alternative source of data for inference of historical processes of in situ speciation and interchange among biogeographical regions. We applied the methodology to explore the historical biogeography of the Qinling Mountains at the boundary of the Oriental and Palaearctic regions. Location The focal area in the Qinling Mountains; sites in Borneo, Panama, and Spain, representing the Oriental, Neotropical and Palaearctic faunas. Time Period Contemporary. Major Taxa Studied Chrysomelidae, a group of ~40,000 species with worldwide distribution. Methods Mass‐trapped insects were subjected to deep Illumina DNA sequencing and mitochondrial genome assembly, followed by phylogenetic analysis and historical biogeographical inference on a dated tree. The methodology produced 622 mitogenomes (304 newly sequenced) each representing a morphologically distinct species. Results Ancestral area reconstruction revealed that the Qinling fauna is a composite of distinct clades that, respectively, have Oriental or Palaearctic ancient origins, while in situ speciation and local clade formation were limited. The global diversity of Chrysomelidae consists of regionalised deep clades at the level of the major zoogeographic realms, which remain recognisable where these realms abut in the Qinling mountains. Yet, the Qinling fauna is clearly distinct from the source areas although local lineage ages are generally Main Conclusions The Qinling fauna is a composite of clades that have either Oriental or Palaearctic origin, indicating the important role of immigration at the realm boundary. Global site‐based phylogenetic analyses based on metagenomic sequencing can address previously intractable questions about the historical biogeography of poorly studied groups even without a fully developed taxonomy.

Micronutrient perspective on COVID-19: Umbrella review and reanalysis of meta-analyses - Yafei Xie; Jianguo Xu; Dan Zhou; Mingyue Guo; Mengxiang Zhang; Ya Gao; Ming Liu; Jiyuan Shi; Kelu Yang; Qingyong Zheng; Liang Zhao; Yu Qin; et al. (Critical Reviews in Food Science and Nutrition, 2024)

Impact of high-altitude environments on the motion and settling characteristics of wet-mix shotcrete dust in tunnels - Guoliang Zhang; Zhongan Jiang; Xiaocuan Li; Ya Chen; Bin Yang; Mingli Si; Rui Feng; Ming Wang (Tunnelling and Underground Space Technology, 2024)

Whole exome sequencing analyses reveal novel genes in telomere length and their biomedical implications - Wei-Shi Liu; Bang-Sheng Wu; Liu Yang; Shi-Dong Chen; Ya-Ru Zhang; Yue-Ting Deng; Xin-Rui Wu; Xiao-Yu He; Jing Yang; Jian-Feng Feng; Wei Cheng; Yu-Ming Xu; et al. (GeroScience, 2024)

North Lhasa terrane in the Precambrian originated from Western Australia - Changsheng Yu; Ming Wang; Di Shen; Mengxian Lin; Shengshuo Zhang; Rui Yang; Danzeng Quewang (Precambrian Research, 2024)

Structurally diverse 1,2-diarylpropanes from the fruit of Crataegus pinnatifida and the investigation on their mirror-image ECD spectra with the same absolute configurations - Tian-Ming Lv; Rui Guo; Bo-Han Yang; Peng Zhao; Bin Lin; Xiao-Xiao Huang; Shao-Jiang Song (Phytochemistry, 2024)

Structure of a histone hexamer bound by the chaperone domains of SPT16 and MCM2 - Songlin Gan; Wen-Si Yang; Liting Wei; Zhiguo Zhang; Rui-Ming Xu (Science China Life Sciences, 2024)

Experimental Study on the Hot Surface Ignition Characteristics and a Predictive Model of Marine Diesel in a Ship Engine Room - Kan Wang; Rui Qiu; Yang Ming; Hang Xu (Journal of Marine Science and Engineering, 2024)
To ensure the safe protection of marine engine systems, it is necessary to explore the hot surface ignition (HSI) characteristics of marine diesel in ship environments. However, an accurate model describing these complex characteristics is still not available. In this work, a new experimental method is proposed in order to enhance prediction performance by integrating testing data of the characteristics of HSI of marine diesel. The sensitivity of HSI is determined by various factors such as surface parameters, flow state, and the ship’s environment. According to variations in the HSI status of marine diesel in an engine room, the HSI probability is distributed in three phases. It is essential to determine whether the presence of marine diesel or surrounding items can intensify the risk of an initial fire beginning in the engine room. A vapor plume model was developed to describe the relationship between HSI height and initial specific buoyancy flux in vertical space. Further, field distribution revealed significant variation in the increase in temperature between 200 and 300 mm of vertical height, indicating a region of initial HSI. In addition, increasing surface temperature did not result in a significant change in ignition delay time. After reaching a temperature of 773 K, the ignition delay time remained around 0.48 s, regardless of how much the hot surface temperature increased. This study reveals the HSI evolution of marine diesel in a ship engine room and develops data-based predictive models for evaluating the safety of HSI parameters during initial accident assessments. The results show that the goodness of fit of the predictive models reached above 0.964. On the basis of the predicted results, the HSI characteristics of marine diesel in engine rooms could be gleaned by actively determining the parameters of risk.

Biotemplated fabrication of N/O co-doped porous carbon confined spinel NiFe2O4 heterostructured mimetics for triple-mode sensing of antioxidants and ameliorating packaging properties - Yuan Gao; Juan Wang; Lin-Lan Zhao; Bo-Yi Yuan; Ya-Nan Kong; Jing-Jing Luo; Shu-Chang Zhao; Wei-Ming Yang; Rui-Lin Liu (Food Chemistry, 2024)

Relationship of solid fuels use with cognitive function and efficacy of switching to cleaner fuels or using ventilation: A systematic review and meta-analysis - Rui Yang; Jie He; Kang-kang Zhong; Ming-xuan Fan; Teng Bao; Xue-Chun Liu; Qi Zhong (Environmental Research, 2024)

Proteomics Sequencing Reveals the Role of TGF-β Signaling Pathway in the Peripheral Blood of Offspring Rats Exposed to Fluoride - Fang-fang Yu; Shui-yuan Yu; Lei-zhen Duan; Shuo Yang; Xiang-bo Hou; Yu-hui Du; Ming-hui Gao; Juan Zuo; Lei Sun; Xiao-li Fu; Zhi-yuan Li; Hui Huang; et al. (Biological Trace Element Research, 2024)

Controlled assembly of novel Fe2O3/MgFe2O4 nanotubular array structures for rapid detection of dibutylamine - Baosheng Li; Junchao Yang; Guanyi Zhang; Ming Zheng; Rui Li; Yubao Kan; Jiahui Li; Tingting Wang; Qibin Huang; Xianfa Zhang; Lihua Huo; Shan Gao; et al. (Chemical Engineering Journal, 2024)

Sesquiterpenoid derivatives isolated from a liquid culture of Hypholoma capnoides 819 - Yu-Ting Wang; Hong-Yu Tan; Xue Zhao; Yu Yang; Rui Xu; Shuai-Ming Zhu; Hao Ma; Fu-Yao Luo; Cai-Hong Dong; Chang-Wei Li (Phytochemistry, 2024)

Leaching and evolution of anthocyanins and aroma compounds during Cabernet Sauvignon wine fermentation with whole-process skin-seed contact - Xue-Chen Yao; Hua-Lin Zhang; Xin-Rui Ma; Nong-Yu Xia; Chang-Qing Duan; Wei-Ming Yang; Qiu-Hong Pan (Food Chemistry, 2024)

Co-application of concentrated biogas slurry and pyroligneous liquor mitigates ammonia emission and sustainably releases ammonium from paddy soil - Zichuan Li; Rui Zhang; Jianfeng Jiang; Yanjun Chai; Haijun Yang; Yutong Zong; Wenbin Tong; Mengting Yuan; Ronghui Li; Lanting Wang; Shengdao Shan; Ming Hung Wong (Science of The Total Environment, 2024)

PD-L1 expression guidance on sintilimab versus pembrolizumab with or without platinum-doublet chemotherapy in untreated patients with advanced non-small cell lung cancer (CTONG1901): A phase 2, randomized, controlled trial - Si-Yang Maggie Liu; Jie Huang; Jia-Yi Deng; Chong-Rui Xu; Hong-Hong Yan; Ming-Yi Yang; Yang-Si Li; E-E Ke; Ming-Ying Zheng; Zhen Wang; Jia-Xin Lin; Bin Gan; et al. (Science Bulletin, 2024)

Nickel isotope fractionation during intense weathering of basalt: Implications for Ni output from continental weathering - Sheng-Sheng Sun; Teng-Hao-Bo Deng; Ming Ao; Wen-Jun Yang; Xiao-Rui Liu; Ting Liu; Jian-Ming Zhu; Jean Louis Morel; Ye-Tao Tang; Rong-Liang Qiu (Geochimica et Cosmochimica Acta, 2024)

Human activity and climate change accelerate the extinction risk to non‐human primates in China - Wen‐Bo Li; Yang Teng; Ming‐Yi Zhang; Ying Shen; Jia‐Wen Liu; Ji‐Wei Qi; Xiao‐Chen Wang; Rui‐Feng Wu; Jin‐Hua Li; Paul A. Garber; Ming Li (Global Change Biology, 2024)
Human activity and climate change affect biodiversity and cause species range shifts, contractions, and expansions. Globally, human activities and climate change have emerged as persistent threats to biodiversity, leading to approximately 68% of the ~522 primate species being threatened with extinction. Here, we used habitat suitability models and integrated data on human population density, gross domestic product (GDP), road construction, the normalized difference vegetation index (NDVI), the location of protected areas (PAs), and climate change to predict potential changes in the distributional range and richness of 26 China's primate species. Our results indicate that both PAs and NDVI have a positive impact on primate distributions. With increasing anthropogenic pressure, species' ranges were restricted to areas of high vegetation cover and in PAs surrounded by buffer zones of 2.7–4.5 km and a core area of PAs at least 0.1–0.5 km from the closest edge of the PA. Areas with a GDP below the Chinese national average of 100,000 yuan were found to be ecologically vulnerable, and this had a negative impact on primate distributions. Changes in temperature and precipitation were also significant contributors to a reduction in the range of primate species. Under the expected influence of climate change over the next 30–50 years, we found that highly suitable habitat for primates will continue to decrease and species will be restricted to smaller and more peripheral parts of their current range. Areas of high primate diversity are expected to lose from 3 to 7 species. We recommend that immediate action be taken, including expanding China's National Park Program, the Ecological Conservation Redline Program, and the Natural Forest Protection Program, along with a stronger national policy promoting alternative/sustainable livelihoods for people in the local communities adjacent to primate ranges, to offset the detrimental effects of anthropogenic activities and climate change on primate survivorship.

The co-regulation of the gut microbiome and host genes might play essential roles in metformin gastrointestinal intolerance - Huixiang Zhang; Jiao Lai; Lihuan Zhang; Wei Zhang; Xun Liu; Qilin Gong; Hongxi Tian; Mingzhi Yang; Tao Yang; Rui Zhao; Dongqing Li; Hehua Huang; et al. (Toxicology and Applied Pharmacology, 2023)

Dual roles of the Arabidopsis PEAT complex in histone H2A deubiquitination and H4K5 acetylation - Si-Yao Zheng; Bin-Bin Guan; Dan-Yang Yuan; Qiang-Qiang Zhao; Weiran Ge; Lian-Mei Tan; Shan-Shan Chen; Lin Li; She Chen; Rui-Ming Xu; Xin-Jian He (Molecular Plant, 2023)

Demethylation-Driven ligase chain reaction for simultaneously sensitive detection of m6A demethylase FTO and m1A demethylase ALKBH3 in breast cancer at Single-Molecule level - Ming-hao Liu; Qian Zhang; Wan-tong Yu; Jian-Ge Qiu; Hui-min Yuan; Chuan-rui Wang; Bing-Hua Jiang; Yan Zhang; Chun-yang Zhang (Chemical Engineering Journal, 2023)

Analysis of spatial and temporal variation of vegetation NPP in Daning River Basin and its driving forces - Wenqian Bai; Li He; Zhengwei He; Xueman Wang; Yang Zhao; Rui Qu; Fang Luo; Xin Chen; Zhifei Wang; Ming Liu (International Journal of Remote Sensing, 2023)

Microplastics affect soil bacterial community assembly more by their shapes rather than the concentrations - Peng-Yang Wang; Ze-Ying Zhao; Xiao-Bin Xiong; Ning Wang; Rui Zhou; Zhi-Ming Zhang; Fan Ding; Meng Hao; Song Wang; Yue Ma; Aimee Grace Uzamurera; Kai-Wen Xiao; et al. (Water Research, 2023)

Rapid imaging approach for marine controlled-source electromagnetic with deployed transmission system - Rui Yang; Xuben Wang; Meng Wang; Xianhu Luo; Ming Deng; Jianen Jing; Kai Chen (Journal of Applied Geophysics, 2023)

The effect of stabilized culture of Lactobacillus rhamnosus GCC-3 on gut and liver health, and anti-viral immunity of zebrafish - Hui Liang; Yadong Xie; Ming Li; Jie Chen; Wenhao Zhou; Rui Xia; Qianwen Ding; Yuanyuan Yao; Zhen Zhang; Yalin Yang; Chao Ran; Zhigang Zhou (Fish & Shellfish Immunology, 2023)

Synchronous regulation of Schottky/p-n dual junction in Prussian blue-derived Janus heterostructures: A path to ultrafast long life potassium ion batteries - Shou-Shan Mai; Kai-Yuan Hsiao; Yi-Chun Yang; Ying-Rui Lu; Ming-Yen Lu; Yi-Yen Hsieh; Che-Bin Chang; Hsing-Yu Tuan (Chemical Engineering Journal, 2023)

Anodic oxidation-accelerated self-reconstruction of tri-metallic Prussian blue analogue toward robust oxygen evolution reaction performance - Thi Xuyen Nguyen; Kai-Hsiang Yang; Yan-Jia Huang; Yen-Hsun Su; Oliver Clemens; Rui-Kun Xie; Yu-Jung Lin; Jyh-Fu Lee; Jyh-Ming Ting (Chemical Engineering Journal, 2023)

Molten Salt-Mediated Surface Reconstruction Induced Orientation-Growth of 1D/2D Heterostructure for High-Sensitivity H2S Gas Sensing - Xuan-Yu Yang; Rui-Jie Zhao; Ke-Feng Xie; Hua Xu; Shao-Ming Fang; Yong-Hui Zhang (Chemical Engineering Journal, 2023)

Unraveling the role of unpaired 3d electrons in e orbital of CoO: Driving π feedback of N2 for efficient ammonia electrosynthesis - Yuanyuan Xiong; Liang Zhao; Rui Zhao; Xiaoxuan Wang; Xinyue Chi; Kaixin Zhang; Zhenzhen Fu; Shuyuan Li; Jiaou Wang; Kaiqi Nie; Zhiyu Yang; Yi-Ming Yan (Chemical Engineering Journal, 2023)

Otolith microchemistry reveals various habitat uses and life histories of Chinese gizzard shad Clupanodon thrissa in the Min River and the estuary, Fujian Province, China - Qing Xu; Qing-qiang Ren; Tao Jiang; Chen-rui Jiang; Lü-ping Fang; Ming-zhe Zhang; Jian Yang; Min Liu (Fisheries Research, 2023)

AIWW: a new nutrition-screening tool for the oncologic population - Yi-Zhong Ge; Zhen-Ming Fu; Qi Zhang; Meng-Meng Song; Guo-Tian Ruan; Xi Zhang; Xiao-Wei Zhang; Xiang-Rui Li; Kang-Ping Zhang; Meng Tang; Xiao-Yue Liu; Ming Yang; et al. (Science China Life Sciences, 2023)

Different dietary fibers unequally remodel gut microbiota and charge up anti-obesity effects - Jia-Jia Wen; Ming-Zhi Li; Jie-Lun Hu; Jiang Wang; Zhi-Qiang Wang; Chun-Hua Chen; Jing-Rui Yang; Xiao-Jun Huang; Ming-Yong Xie; Shao-Ping Nie (Food Hydrocolloids, 2023)

Selenium toxicity and bioaccumulation in selenium-enriched fly (Chrysomya megacephala) maggots - Rui Jie Peng; Chao Zheng; Zhan Biao Yang; Xiao Xun Xu; Ming Hung Wong; Yu Bon Man; Zhang Cheng (Environmental Geochemistry and Health, 2023)

Euphpepluone S, a new lathyrane diterpenoid with anti-inflammatory activity from Euphorbia peplus L. - Shi-Peng Guan; Ying Yang; Mao Sun; Min Cai; Xue-Xue Pu; Jian-Yi Huang; Ping Yi; Lin Liu; Ming-Rui Yuan; Yuan-Yuan Cheng; Ying-Tong Di (Phytochemistry Letters, 2023)

Chemical constituents from Ajuga macrosperma Wall. ex Benth. (Lamiaceae) and their chemotaxonomic significance - Hua-Yi Jiang; Yi-Huan Li; Qian-Ru Zhang; Dan Teng; Ming-Ming Li; Rui Yang; Hong-Ping He (Biochemical Systematics and Ecology, 2023)

Manipulating electron redistribution of active sites by in situ engineering B-S-V bond in VS2 catalyst for stable nitrogen fixation - Xinyue Chi; Rui Zhao; Xiaoxuan Wang; Yuanyuan Xiong; Kaixin Zhang; Zhenzhen Fu; Yebo Yao; Shuyuan Li; Zhi-Yu Yang; Yi-Ming Yan (Chemical Engineering Journal, 2023)

Comparative transcriptomes analysis of the ovary reveals potential ovarian development-related genes and pathways in Macrobrachium rosenbergii - Yan-Hao Yang; Rui Wang; Ming Li; Hui-Zan Yang; Guang-Hua Huang; Ke-Yi Ma; Gao-Feng Qiu; Yong Lin (Invertebrate Reproduction & Development, 2023)

Tea polyphenol and epigallocatechin gallate ameliorate hyperlipidemia via regulating liver metabolism and remodeling gut microbiota - Jia-Jia Wen; Ming-Zhi Li; Chun-Hua Chen; Tao Hong; Jing-Rui Yang; Xiao-Jun Huang; Fang Geng; Jie-Lun Hu; Shao-Ping Nie (Food Chemistry, 2023)

Mobile Phone Imaging Point Cloud Modelling for 3D Recording and Measurement of Small Scenes of Suspected Fossil Outcrops Found in the Field - Gao Sha; Gan Shu; Yuan Xiping; Hu Lin; Bi Rui; Li Raobo; Yang Ming (Geoheritage, 2023)

MiR-130/SNAP-25 axis regulate presynaptic alteration in anterior cingulate cortex involved in lead induced attention deficits - Tao Wang; Rui-Li Guan; Yun-Feng Zou; Gang Zheng; Xue-Feng Shen; Zi-Peng Cao; Rui-Hua Yang; Ming-Chao Liu; Ke-Jun Du; Xue-Hang Li; Michael Aschner; Ming-Gao Zhao; et al. (Journal of Hazardous Materials, 2023)

Different roles of primary and secondary sources in reducing PM2.5: Insights from molecular markers in Pearl River Delta, South China - Kong Yang; Duo-Hong Chen; Xiang Ding; Jun Li; Yu-Qing Zhang; Tao Zhang; Qiao-Yun Wang; Jun-Qi Wang; Qian Cheng; Hao Jiang; Ping Liu; Zi-Rui Wang; et al. (Atmospheric Environment, 2023)

Bioactive icetexane and abietane diterpenes from Isodon phyllopodus - Rui Deng; Juan Zou; Chen-Liang Zhao; Ye-Meng Yang; Chuen Fai Ku; Yu Zhu; Zheng-Ming Liang; Jiang-Hai Ye; Lu-Tai Pan; Hong-Jie Zhang (Natural Product Research, 2023)

Naïve-like conversion of bovine induced pluripotent stem cells from Sertoli cells - Yu Jiang; Ning-Ning Cai; Xing-Lan An; Wen-Qian Zhu; Rui Yang; Bo Tang; Zi-Yi Li; Xue-Ming Zhang (Theriogenology, 2023)

Patternable thermal conductive interface materials enabled by vitrimeric phase change materials - Li-Mei Peng; Zhao Xu; Jie Yang; Lu Bai; Rui-Ying Bao; Ming-Bo Yang; Wei Yang (Chemical Engineering Journal, 2023)

Multifunctional lysosome-targetable fluorescent probe for imaging peroxynitrite in acute liver injury model - Kai Wang; Rui Guo; Xu-Yang Chen; Yu-Shun Yang; Lu-Qin Qiao; Ming-Lin Wang (Chemical Engineering Journal, 2023)

Solar ring mission: Building a panorama of the Sun and inner-heliosphere - Yuming Wang; Xianyong Bai; Changyong Chen; Linjie Chen; Xin Cheng; Lei Deng; Linhua Deng; Yuanyong Deng; Li Feng; Tingyu Gou; Jingnan Guo; Yang Guo; et al. (Advances in Space Research, 2023)

Construction of a target MSNs drugcarrier loaded with siRNAGLI1 and siRNASMO aim at hedgehog signal pathway and the pharmacodynamic study of drug-carriers in the treatment of leukemia stem cells - Yuan Zhang; Rui Cai; HaiJun Li; Yu Duan; Yan Zhang; Wei Jing; ShaoGang Lv; Xi Chu; Zheng Cao; Lei Yang; Liang Ming (Drug Delivery and Translational Research, 2022)

Assessing trophic interactions among three tuna species in the Solomon Islands based on stomach contents and stable isotopes - Ri Jin Jiang; Fan Yang; Feng Chen; Rui Yin; Ming Zhi Liu; Wen Bin Zhu; Ai Guo; Lian Wei Liu (Frontiers in Marine Science, 2022)
Trophic research is essential to the conservation and management of fishery resources. This study analyzed the feeding habits and nutritional interactions among three tuna species in the waters of the Solomon Islands (5°12′S–15°20′S, 157°31′E–172°19′E). A total of 103 bigeye tuna ( Thunnus obesus ), 296 yellowfin tuna ( Thunnus albacores ), and 264 albacore tuna ( Thunnus alalunga ) samples were collected from September to December 2019. Samples for stomach content and stable isotope analysis were randomly selected. The stomach content analysis results showed that the stomach contents of the three tuna species were rich in prey, and 48 prey species were identified, including fish, cephalopods, and crustaceans, with high between-phenotype component (BPC). Yellowfin tuna consumed the largest variety of food and bigeye tuna consumed the smallest. The feeding intensity of bigeye tuna were higher than that of yellowfin and albacore tuna. Yellowfin tuna had the highest empty stomach rate (35.69%) and lowest average stomach fullness index (0.064). The degree of stomach fullness in the three tuna species was mainly 1, and the difference in the stomach fullness index among them was significant ( P <0.001). Food overlap (0.3–0.6) and Levins index (<0.6) among the three species were low, indicating a specialized feeding tendency. Bigeye tuna mainly feed on Ommastrephes bartrami and Myctophidae, yellowfin tuna mainly feed on Hyperiidea and Aluterus monoceros , and albacore tuna mainly feed on Gempylus serpens and Loligo chinensis . The stable isotope results showed that the δ 13 C and δ 15 N values of the three tuna species were significant ( P <0.001). The standard ellipse area corrected for small sample sizes (SEAc) and total niche area (TA) of bigeye tuna, range of δ 15 N (NR) of yellowfin tuna, and range of δ 13 C (CR) of albacore tuna were the highest. The results of this study will help improve our understanding of the feeding ecology of these three tuna species and their important roles in the ecosystem and food web structure.

Long non‑coding RNA PART1: dual role in cancer - Rui Ran; Chao-Yang Gong; Zhi-Qiang Wang; Wen-Ming Zhou; Shun-Bai Zhang; Yong-Qiang Shi; Chun-Wei Ma; Hai-Hong Zhang (Human Cell, 2022)

Otolith Marking With Strontium for Stock Assessment in Coilia nasus - Ming-Zhi Liu; Ri-jin Jiang; Hui Zhang; Fan Yang; Xia-Fang Li; Guang-Peng Feng; Rui Yin; Feng Chen (Frontiers in Marine Science, 2022)
Mass stock enhancement and release are excellent ways to recover Coilia nasus resources. However, it is challenging to evaluate stock enhancement effectively, and it is important to establish a method suitable for estimating C. nasus populations. We explored the effectiveness of marking otoliths in these fish with strontium by immersing C. nasus in hexahydrate strontium chloride solutions. We used laser ablation inductively coupled plasma mass spectrometry to measure the strontium content of otoliths and fish bodies. The larvae (40 d post hatch) were reared in five different concentrations of strontium (0, 12, 24, 48, and 60 mg/L) for 7 d, followed by treatment in non-additive water for 3 wk. The results showed that the cumulative mortality rate was not significantly different between treatment and control groups ( P >0.05), except in the group treated with 24 mg/L strontium. The swimming and feeding behaviors did not change significantly, indicating that strontium did not negatively affect survival in this species. The strontium/calcium ratios of otoliths in the control group were stable (1.78–2.32 mmol/mol), whereas those of the experimental (marked) groups ranged widely (4.47–61.02 mmol/mol). The strontium/calcium ratios increased with increasing strontium concentration, but gradually returned to baseline values, resulting in a 100% success rate of marking with strontium. Following immersion in 12 mg/L strontium, strontium levels in the body returned to normal after 24 d. In summary, a treatment of 12 mg/L strontium for 4 d was identified as viable for marking. We confirmed the feasibility of strontium marking for the mass marking and release of C. nasus . This marking method does not affect the physiology of the fish and may provide a new approach for reasonable and scientific stock assessment of C. nasus post hatch.

Extracellular vesicles derived from human Sertoli cells: characterizations, proteomic analysis, and miRNA profiling - Xiao-Hui Tan; Sheng-Ji Gu; Wen-Jie Tian; Wen-Peng Song; Yang-Yang Gu; Yi-Ming Yuan; Xue-Song Li; Zhong-Cheng Xin; Sae Woong Kim; Rui-Li Guan; Woong Jin Bae (Molecular Biology Reports, 2022)

Flavonoid glycosides from the nectar of Camellia reticulata Lindl. - Xin-Lan Chen; Xing-Rong Peng; Xue-Yang Gong; Yi-Qiu Liu; Zhuo Qing; Xiao-Xiao Ren; Rui Su; Li-Ming Fang; Ming-Hua Qiu; Kun Dong (Natural Product Research, 2022)

A feasible vibration measurement and active control method of reinforced concrete lightweight pier railway bridges for heavy-haul monorail trains - Ling-kun Chen; Li-zhong Jiang; Rui Li; Qiao Li; Ming Zhang; Nan Zhang; Jin-zhang Luo; Liang Ling; Sheng-yang Zhu (European Journal of Environmental and Civil Engineering, 2022)

Effects of organic acids on the chemotaxis profiles and biocontrol traits of antagonistic bacterial endophytes against root-rot disease in Panax notoginseng - Li Ma; Wu-Qin Wang; Rui Shi; Xue-Mei Zhang; Xin Li; Yu-Sen Yang; Ming He Mo (Antonie van Leeuwenhoek, 2021)

lncRNA SNHG16 Mediates Cell Proliferation and Apoptosis in Cholangiocarcinoma by Directly Targeting miR-146a-5p/GATA6 Axis - Tao Wu; Ming-Sheng Lei; Xu-Zhao Gao; Ting-Gang Xiong; Kang Yang; Qian Gong; Rui Tang; Yue-Peng Tian; Xiao-Hua Fu (Biochemical Genetics, 2021)

Structure–activity relationship studies on Pd176252 derivatives leading to discovery of novel GRP receptor antagonist with potent anticancer activity - Ming-jun Yu; Chao Li; Meng He; Yu-ting Zhu; Rui Yang; Sheng-song Deng; Xiao-ming Meng; Ri-sheng Yao (Medicinal Chemistry Research, 2021)

Quantitative Proteomics Analysis of Sugarcane Ratoon Crop Chlorosis - Ye-Geng Fan; Rong-Fa Chen; Li-Hang Qiu; Zhong-Feng Zhou; Hui-Wen Zhou; Ji-Guang Wei; Xiu-Peng Song; Ting Luo; Prakash Lakshmanan; Xing Huang; Jian-Ming Wu; Yang-Rui Li (Sugar Tech, 2021)

Effects of hydrological change on the risk of riverine algal blooms: case study in the mid-downstream of the Han River in China - Lisha Shen; Ming Dou; Rui Xia; Guiqiu Li; Baiheng Yang (Environmental Science and Pollution Research, 2021)

Arbuscular mycorrhizal colonization rate of an exotic plant, Galinsoga quadriradiata, in mountain ranges changes with altitude - Gang Liu; Rui-Ling Liu; Wen-Gang Zhang; Ying-Bo Yang; Xiao-Qiong Bi; Ming-Zhu Li; Xiao-Yan Chen; Hua Nie; Zhi-Hong Zhu (Mycorrhiza, 2021)

Astrocyte-Derived Lactate Modulates the Passive Coping Response to Behavioral Challenge in Male Mice - Ya-Nan Yin; Jian Hu; Yi-Li Wei; Ze-Lin Li; Zhou-Cai Luo; Rui-Qi Wang; Ke-Xin Yang; Shu-Ji Li; Xiao-Wen Li; Jian-Ming Yang; Tian-Ming Gao (Neuroscience Bulletin, 2021)

A review of the Chinese monotypic genus Melliodendron (Styracaceae), with a new synonym of M. xylocarpum - Xue-Hui Wu; Rui Zhang; Timothy M. A. Utteridge; Yu-Lin Liu; Guang-Yao Yang; Ming Tang (Kew Bulletin, 2020)

One new sterpurane sesquiterpene from cultures of the basidiomycete Pholiota nameko - Wan-Rong Niu; Cong-Liang Guo; Deng-Ji Lou; Rui-Ting Li; Qiao Xiang; Yu-Lin Zou; Xiu-Ming Cui; Xiao-Yan Yang (Natural Product Research, 2020)

Intrusion of Fall Armyworm (Spodoptera frugiperda) in Sugarcane and Its Control by Drone in China - Xiu-Peng Song; Yong-Jian Liang; Xiao-Qiu Zhang; Zhen-Qiang Qin; Jin-Ju Wei; Yang-Rui Li; Jian-Ming Wu (Sugar Tech, 2020)

Effects of Spray Parameters of Drone on the Droplet Deposition in Sugarcane Canopy - Xiao-Qiu Zhang; Xiu-Peng Song; Yong-Jian Liang; Zhen-Qiang Qin; Bao-Qing Zhang; Jin-Ju Wei; Yang-Rui Li; Jian-Ming Wu (Sugar Tech, 2020)

Mapping and characterization of major QTL for spike traits in common wheat - Cheng-Hao Kuang; Xiao-Fang Zhao; Ke Yang; Zhi-Peng Zhang; Li Ding; Zhi-En Pu; Jian Ma; Qian-Tao Jiang; Guo-Yue Chen; Ji-Rui Wang; Yu-Ming Wei; You-Liang Zheng; et al. (Physiology and Molecular Biology of Plants, 2020)

Uptake and accumulation of pentachloronitrobenzene in pak choi and the human health risk - Ming Li; Guanghui Xu; Rui Yu; Yang Wang; Yong Yu (Environmental Geochemistry and Health, 2020)

Effects of Exogenous GA3 and DPC Treatments on Levels of Endogenous Hormone and Expression of Key Gibberellin Biosynthesis Pathway Genes During Stem Elongation in Sugarcane - Li-Hang Qiu; Rong-Fa Chen; Han-Min Luo; Ye-Geng Fan; Xing Huang; Jun-Xian Liu; Fa-Qian Xiong; Hui-Wen Zhou; Chong-Kun Gan; Jian-Ming Wu; Yang-Rui Li (Sugar Tech, 2019)

Specimen shape and cross-section effects on the mechanical properties of rocks under uniaxial compressive stress - Kun Du; Rui Su; Ming Tao; Chengzhi Yang; Aliakbar Momeni; Shaofeng Wang (Bulletin of Engineering Geology and the Environment, 2019)

De novo assembly and transcriptome analysis of differentially expressed genes relevant to variegation in hawthorn flowers - Wei Ji; Wei Zhao; Rong-Chen Liu; Xiao-Bo Jiao; Kai Han; Zhong-Yi Yang; Mei-Ying Gao; Rui Ren; Xiu-Juan Fan; Ming-Xia Yang (Plant Biotechnology Reports, 2019)

Two new sesquiterpenes from cultures of the higher fungus Pholiota nameko - Xiao-Yan Yang; Wan-Rong Niu; Rui-Ting Li; Xiu-Ming Cui; Ji-Kai Liu (Natural Product Research, 2019)

A reliable non-invasive PCR method for takin (Budorcas taxicolor) sex identification based on amelogenin gene - Ming Zhou; Jiaojiao Yu; Rui Xue; Biao Li; Jiandong Yang (Conservation Genetics Resources, 2019)

A new polyketide purpurogenic acid: the activated production of polyketides by the diethyl sulphate mutagenesis of marine-derived Penicillium purpurogenum G59 - Ming-Wen Xia; Yu Yang; Rui Xu; Chang-Wei Li; Cheng-Bin Cui (Natural Product Research, 2019)

Cloning and Identification of Differentially Expressed Genes Associated with Smut in Sugarcane - Xiu-Peng Song; Dan-Dan Tian; Ming-Hui Chen; Zhen-Qiang Qin; Jin-Ju Wei; Chun-Yan Wei; Xiao-Qiu Zhang; De-Wei Li; Li-Tao Yang; Yang-Rui Li (Sugar Tech, 2018)

Acupuncture Prevents the Impairment of Hippocampal LTP Through β1-AR in Vascular Dementia Rats - Ling-Yong Xiao; Xue-Rui Wang; Jing-Wen Yang; Yang Ye; Wen Zhu; Yan Cao; Si-Ming Ma; Cun-Zhi Liu (Molecular Neurobiology, 2018)

Nutrient Decomposition Rate and Sugarcane Yield as Influenced by Mung Bean Intercropping and Crop Residue Recycling - Tie-Guang He; Li-Rong Su; Yang-Rui Li; Tian-Ming Su; Fang Qin; Qin Li (Sugar Tech, 2018)

The root transcriptome of Achyranthes bidentata and the identification of the genes involved in the replanting benefit - Yan Hui Yang; Ming Jie Li; Yan Jie Yi; Rui Fang Li; Cheng Dong; Zhong Yi Zhang (Plant Cell Reports, 2018)

Effects of fine particle content and sample scale on the failure properties of loose landslide deposits - Bin-rui Gan; Xing-guo Yang; Ming-liang Chen; Jia-wen Zhou (Arabian Journal of Geosciences, 2018)

Spatial trends and pollution assessment for mercury in the surface soils of the Nansi Lake catchment, China - Ming-Yi Ren; Li-Yuan Yang; Long-Feng Wang; Xue-mei Han; Jie-Rui Dai; Xu-Gui Pang (Environmental Science and Pollution Research, 2018)

TQ-B3203, a potent proliferation inhibitor derived from camptothecin - Xiquan Zhang; Meng Cao; Jing Xing; Fei Liu; Ping Dong; Xin Tian; Hongjiang Xu; Laifang Zhang; Hongmei Gu; Ling Yang; Rui Li; Ming Zheng; et al. (Medicinal Chemistry Research, 2017)

Endothelial Progenitor Cells’ Classification and Application in Neurological Diseases - Jing-jing Yuan; Jing Yang; Shi-lei Sun; Rui Zhang; Yu-ming Xu (Tissue Engineering and Regenerative Medicine, 2017)

A simple method for removing low-density granulocytes to purify T lymphocytes from peripheral blood mononuclear cells - Si-gong Zhang; Yu-xin Song; Xiao-ming Shu; Hai-li Shen; Han-bo Yang; Rui-xue Duo; Guo-chun Wang (Journal of Zhejiang University-SCIENCE B, 2017)

Land use legacies and nitrogen fertilization affect methane emissions in the early years of rice field development - Rui Shao; Ming Xu; Renqiang Li; Xiaoqin Dai; Lixiang Liu; Ye Yuan; Huimin Wang; Fengting Yang (Nutrient Cycling in Agroecosystems, 2017)

Characterization of a neutral recombinant xylanase from Thermoactinospora rubra YIM 77501T - Yi-Rui Yin; Qing-Wen Hu; Wen-Dong Xian; Feng Zhang; En-Min Zhou; Hong Ming; Min Xiao; Xiao-Yang Zhi; Wen-Jun Li (Antonie van Leeuwenhoek, 2017)

Hydrogen‐rich water regulates effects of ROS balance on morphology, growth and secondary metabolism via glutathione peroxidase in Ganoderma lucidum - Ang Ren; Rui Liu; Zhi‐Gang Miao; Xue Zhang; Peng‐Fei Cao; Tian‐Xi Chen; Chen‐Yang Li; Liang Shi; Ai‐Liang Jiang; Ming‐Wen Zhao (Environmental Microbiology, 2017)
Summary Ganoderma lucidum is one of the most important medicinal fungi, but the lack of basic study on the fungus has hindered the further development of its value. To investigate the roles of the redox system in G. lucidum , acetic acid (HAc) was applied as a reactive oxygen species (ROS) stress inducer, and hydrogen‐rich water (HRW) was used to relieve the ROS stress in this study. Our results demonstrate that the treatment of 5% HRW significantly decreased the ROS content, maintained biomass and polar growth morphology of mycelium, and decreased secondary metabolism under HAc‐induced oxidative stress. Furthermore, the roles of HRW were largely dependent on restoring the glutathione system under HAc stress in G. lucidum . To provide further evidence, we used two glutathione peroxidase (GPX)‐defective strains, the gpxi strain, the mercaptosuccinic acid (MS, a GPX inhibitor)‐treated wide‐type (WT) strain, and gpx overexpression strains for further research. The results show that HRW was unable to relieve the HAc‐induced ROS overproduction, decreased biomass, mycelium morphology change and increased secondary metabolism biosynthesis in the absence of GPX function. The gpx overexpression strains exhibited resistance to HAc‐induced oxidative stress. Thus, we propose that HRW regulates morphology, growth and secondary metabolism via glutathione peroxidase under HAc stress in the fungus G. lucidum . Furthermore, our research also provides a method to study the ROS system in other fungi.

Sugar Industry and Improved Sugarcane Farming Technologies in China - Yang-Rui Li; Xiu-Peng Song; Jian-Ming Wu; Chang-Ning Li; Qiang Liang; Xi-Hui Liu; Wei-Zan Wang; Hong-Wei Tan; Li-Tao Yang (Sugar Tech, 2016)

Effects of short-term inflammatory and/or hypoxic pretreatments on periodontal ligament stem cells: in vitro and in vivo studies - Yang Yu; Chun-Sheng Bi; Rui-Xin Wu; Yuan Yin; Xi-Yu Zhang; Ping-Heng Lan; Fa-Ming Chen (Cell and Tissue Research, 2016)

New alkaloids from the leaves of Evodia rutaecarpa - Xiao Xia; Jian-Guang Luo; Rui-Huan Liu; Ming-Hua Yang; Ling-Yi Kong (Natural Product Research, 2016)

Inoculation of Fe/Mn-oxidizing bacteria enhances Fe/Mn plaque formation and reduces Cd and As accumulation in Rice Plant tissues - Ming Fang Dong; Ren Wei Feng; Rui Gang Wang; Yang Sun; Yong Zhen Ding; Ying Ming Xu; Zhi Lian Fan; Jun Kang Guo (Plant and Soil, 2016)

Structure and expression of phosphoglucan phosphatase genes of Like Sex Four1 and Like Sex Four2 in barley - Jian Ma; Shang Gao; Qian-Tao Jiang; Qiang Yang; Min Sun; Ji-Rui Wang; Peng-Fei Qi; Ya-Xi Liu; Wei Li; Zhi-En Pu; Xiu-Jin Lan; Yu-Ming Wei; et al. (Genetica, 2016)

Canyon-related undulation structures in the Shenhu area, northern South China Sea - Shaohua Qiao; Ming Su; Zenggui Kuang; Rui Yang; Jinqiang Liang; Nengyou Wu (Marine Geophysical Research, 2015)

Migration of methane associated with gas hydrates of the Shenhu Area, northern slope of South China Sea - Rui Yang; Ming Su; Shaohua Qiao; Xiaorong Cong; Zheng Su; Jinqiang Liang; Nengyou Wu (Marine Geophysical Research, 2015)

Preparation of malathion MIP-SPE and its application in environmental analysis - Hai Gen Zuo; Jian Xin Zhu; Chun Rui Zhan; Lei Shi; Ming Xing; Ping Guo; Yuan Ding; Hong Yang (Environmental Monitoring and Assessment, 2015)

Effects of Exogenous Abscisic Acid on Cell Membrane and Endogenous Hormone Contents in Leaves of Sugarcane Seedlings under Cold Stress - Xing Huang; Ming-Hui Chen; Li-Tao Yang; Yang-Rui Li; Jian-Ming Wu (Sugar Tech, 2015)

Molecular Cloning and Functional Analysis of an Ethylene Receptor Gene from Sugarcane (Saccharum spp.) by Hormone and Environmental Stresses - Ai-Qin Wang; Xing-Zhi Ye; Jing-Li Huang; Jun-Qi Niu; Ming Liu; Yong-Bao Pan; Li-Tao Yang; Yang-Rui Li (Sugar Tech, 2015)

Upregulation of HIF-1α Via Activation of ERK and PI3K Pathway Mediated Protective Response to Microwave-Induced Mitochondrial Injury in Neuron-Like Cells - Li Zhao; Yue-Feng Yang; Ya-Bing Gao; Shui-Ming Wang; Li-Feng Wang; Hong-Yan Zuo; Ji Dong; Xin-Ping Xu; Zhen-Tao Su; Hong-Mei Zhou; Ling-Ling Zhu; Rui-Yun Peng (Molecular Neurobiology, 2014)

The metabolism of 8-heptadecene in Pyropia (Bangiaceae, Rhodophyta) - Min Zhang; Rui-Xia Li; Chuan-Ming Hu; Li-En Yang; Jun Tang; Qin-Qin Lu; Tao Zhang; Zong-Gen Shen; Song-Dong Shen; Pu Xu; Jian-Yi Zhu (Journal of Applied Phycology, 2014)

Plant diversity as a good indicator of vegetation stability in a typical plateau wetland - Wei Li; Rui Tan; Yu-ming Yang; Juan Wang (Journal of Mountain Science, 2014)

Phytoremediation potential of Pteris vittata L. under the combined contamination of As and Pb: beneficial interaction between As and Pb - Xiao-ming Wan; Mei Lei; Tong-bin Chen; Guang-dong Zhou; Jun Yang; Xiao-yong Zhou; Xi Zhang; Rui-xiang Xu (Environmental Science and Pollution Research, 2014)

Effects of Ethephon on Key Enzymes of Sucrose Metabolism in Relation to Sucrose Accumulation in Sugarcane - Ai-Qin Wang; Wen-Jing Huang; Jun-Qi Niu; Ming Liu; Li-Tao Yang; Yang-Rui Li (Sugar Tech, 2013)

Arbuscular mycorrhizal fungal diversity, external mycelium length, and glomalin-related soil protein content in response to long-term fertilizer management - Jue Dai; Junli Hu; Xiangui Lin; Anna Yang; Rui Wang; Jiabao Zhang; Ming Hung Wong (Journal of Soils and Sediments, 2013)

Effect of Long-Term Vinasse Application on Physico-chemical Properties of Sugarcane Field Soils - Ze-Pu Jiang; Yang-Rui Li; Guang-Po Wei; Qing Liao; Tian-Ming Su; Yan-Cheng Meng; Hai-Ying Zhang; Chang-Yan Lu (Sugar Tech, 2012)

Macronutrients Absorption and Surface Runoff Losses Under Different Fertilizer Treatments in Sugarcane Field - Tian-Ming Su; Yang-Rui Li; Guang-Po Wei; Ze-Pu Jiang; Qing Liao; Shu-Biao Zhu (Sugar Tech, 2012)

Changes in soil biochemical properties associated with Ligularia virgaurea spreading in grazed alpine meadows - Xiao Ming Shi; Xiao Gang Li; Rong Mei Wu; Yun Hui Yang; Rui Jun Long (Plant and Soil, 2011)

A new bioorganic fertilizer can effectively control banana wilt by strong colonization with Bacillus subtilis N11 - Nan Zhang; Kai Wu; Xin He; Shu-qing Li; Zhen-hua Zhang; Biao Shen; Xing-ming Yang; Rui-fu Zhang; Qi-wei Huang; Qi-rong Shen (Plant and Soil, 2011)

Evaluation of Genetic Manipulation Strategies on d-Lactate Production by Escherichia coli - Li Zhou; Zhi-Rui Zuo; Xian-Zhong Chen; Dan-Dan Niu; Kang-Ming Tian; Bernard A. Prior; Wei Shen; Gui-Yang Shi; Suren Singh; Zheng-Xiang Wang (Current Microbiology, 2011)

Isolation and simultaneous determination of two benzofurans in Radix Eupatorii Chinensis - Xiao-Ling Xie; Xin-Jun Xu; Rui-Ming Li; Jin-Zhi Wan; Chun-Yan Xie; De-Po Yang; Xiao Chen (Natural Product Research, 2010)

Inhibitor of DNA binding-1 promotes the migration and proliferation of endothelial progenitor cells in vitro - Hong Wang; Yang Yu; Rui-wei Guo; Yan-kun Shi; Ming-bao Song; Jian-fei Chen; Shi-yong Yu; Yang-guang Yin; Pan Gao; Lan Huang (Molecular and Cellular Biochemistry, 2010)

Infectivity and propagation of attenuated infectious bursal disease virus in the chicken B-lymphocyte cell line DT40 - Jun Luo; Gai-Ping Zhang; Jian-Ming Fan; Man Teng; Lei-Ming You; Ling Zhou; Rui-Guang Deng; Xuan-Nian Wang; Yan-Yan Yang; Li Wang; Guang-Xu Xing; Na Cheng (Archives of Virology, 2009)

Deglycosylation altered the gating properties of rNav1.3: glycosylation/deglycosylation homeostasis probably complicates the functional regulation of voltage-gated sodium channel - Qing Xu; Hui-Wen Cheng; Hui-Qiong He; Zhi-Rui Liu; Ming He; Hong-Tian Yang; Zhi-Lei Zhou; Yong-Hua Ji (Neuroscience Bulletin, 2008)

Ore-forming fluids associated with granite-hosted gold mineralization at the Sanshandao deposit, Jiaodong gold province, China - Hong Rui Fan; Ming Guo Zhai; Yi Han Xie; Jin Hui Yang (Mineralium Deposita, 2003)

Contributory presentations/posters - N. Manoj; V. R. Srinivas; A. Surolia; M. Vijayan; K. Suguna; R. Ravishankar; K. Suguna; A. Surolia; M. Vijayan; R. Schwarzenbacher; K. Zeth; Diederichs; et al. (Journal of Biosciences, 1999)